An out-of-plane rotational energy harvesting system for low frequency environments. (15th November 2017) - Febbo, M.; Machado, S.P.; Gatti, C.D.; Ramirez, J.M.
Graphical abstract: Highlights: An alternative to cantilever beam-type systems for energy harvesting is proposed. The device generates energy in a low frequency rotational environment. It comprises two beams, a spring and two heavy masses joined by the spring. By varying the flexibility of one beam, the device increments output DC power. The generated DC power suffices to feed low power wireless transmitters. Abstract: We present a novel design of a rotational power scavenging system as an alternative to cantilever beams attached to a hub. The device is meant to provide energy to wireless autonomous monitoring systems in low frequency environments such as wind turbines of 30 kW with rotational speeds of between 50 and 150 rpm. These characteristics define the bandwidth of the rotational energy harvesting system (REH) and its physical dimensions. A versatile geometric configuration with two elastic beams and two heavy masses joined by a spring is proposed. A piezoelectric sheet is mounted on the primary beam while the REH is placed on a rotating hub with the gravitational force acting as a periodic source. This kind of double-beam system offers the possibility to modify the vibration characteristics of the harvester for achieving high power density. An analytical framework using the Lagrangian formulation is derived to describe the motion of the system and the voltage output as a function of rotation speed. Several sets of experiments were performed to characterize the system and to validate the assumed hypothesis. In the experimental setup, a wireless data acquisition system based on Arduino technology was implemented to avoid slip-ring mechanisms. The results show very good agreement between the theoretical and experimental tests. Moreover, the output power of a simple harvesting circuit, which serves as an energy storage device, yields values ranging 26–105 μW over the whole frequency range. This allows us to use the proposed device for the designed purpose, taking into account the power requirements of commercially available wireless transmitter systems.